Gene transcript accumulation and enzyme activity of β-amylases suggest involvement in the starch depletion during the ripening of cherry tomatoes - Maria, Thanou; Tsaniklidis, Georgios; Delis, Costas; Nikolopoulou, Aimilia Eleni; Nikoloudakis, Nikolaos; Karapanos, Ioannis; Aivalakis, Georgios (My University, 2016)
© 2015 The Authors. Published by Elsevier B.V. All rights reserved. The flavor of tomato fruits is mostly influenced by the accumulation of sugars and organic acids. During fruit ripening a conversion of starch to sugars occurs, which modulates significantly the taste and consequently the quality of the ripe tomato fruits. β-Amylases, a group of major starch hydrolytic enzymes involved in starch degradation were examined in developing cherry tomatoes. Our results suggest that the enzyme activity and the gene transcript accumulation of plastidial β-amylase isoenzymes were elevated during the late stages of fruit development indicating a participation of the enzyme in starch depletion and in the increase of total soluble sugar levels in ripe tomatoes.
Keywords: Beta amylase; Enzyme activity; Gene expression; Starch; Tomato fruit